Synthesis of bioplastics from paddy waste - Nabilah Afiqah Binti Suhaimi (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
In this research, bioplastics was ochestrated from paddy waste by processing it with trifluoroacetic acid (TFA), casting, and evaporation. The high cellulose content in the paddy has making it as the best preface for solid to synthesis bioplasticks. Two major laboratory test was done to test the chemical and morphological and thermo-mechanical propertieson each films produced. Based on X-ray diffraction (XRD) analysis, films which contain paddy materials showed the higher peak intensity than films which originating from MCC only. The morphology or surface structure of the films that was analyzed using field emission scanning electron microscope (FESEM) and atomic force microscope (AFM), showing a bioplastics surface. Overally, the mechanical and chemical propeties of the bioplastics that was synthesized from paddy waste had slightly observed to have the same mechanical and chemical properties with platics which derived from petroleum.